2014
DOI: 10.1111/tpj.12478
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins inhibit adventitious rooting in hybrid aspen and Arabidopsis by affecting auxin transport

Abstract: SUMMARYKnowledge of processes involved in adventitious rooting is important to improve both fundamental understanding of plant physiology and the propagation of numerous plants. Hybrid aspen (Populus tremula 3 tremulo€ ıdes) plants overexpressing a key gibberellin (GA) biosynthesis gene (AtGA20ox1) grow rapidly but have poor rooting efficiency, which restricts their clonal propagation. Therefore, we investigated the molecular basis of adventitious rooting in Populus and the model plant Arabidopsis. The product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 43 publications
1
82
0
1
Order By: Relevance
“…Together with other substances, they act in the induction of rhizogenesis (WOODWARD;BARTEL, 2005;SAUER et al, 2013), suggesting the importance of cuttings position in branch (topophysis) on the quantity of rooting promoting substances, like auxins and carbohydrates. These substances carry out an essential function in the construction of necessary cellular structures for all plant physiological processes (LI et al, 2009;DENAXA et al, 2012;MAURIAT et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Together with other substances, they act in the induction of rhizogenesis (WOODWARD;BARTEL, 2005;SAUER et al, 2013), suggesting the importance of cuttings position in branch (topophysis) on the quantity of rooting promoting substances, like auxins and carbohydrates. These substances carry out an essential function in the construction of necessary cellular structures for all plant physiological processes (LI et al, 2009;DENAXA et al, 2012;MAURIAT et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological functions of GA in root growth have been discussed for Arabidopsis (Tanimoto 2012;Mauriat et al 2014) and crosstalk between indole-3-acetic acid (IAA) and GA has been demonstrated in the signaling system (Fu and Harberd 2003;Gou et al 2010). Supplementation of GA 3 was reported to induce increases in secondary metabolite production and also affected cell viability and root morphogenesis of E. purpurea in hairy root cultures (Abbasi et al 2012).…”
Section: In Vitro Plantlet Regenerationmentioning
confidence: 99%
“…This consequently reduces auxin availability required for the induction of cell division (Mauriat et al, 2014;Niu et al, 2013). Despite its negative effect, GA was shown to promote AR formation through interactions with ethylene in deep water rice (Steffens et al, 2006).…”
Section: Other Growth Regulatorsmentioning
confidence: 99%
“…AR formation is a complex heritable trait controlled by many endogenous and exogenous factors including light conditions, temperature, hormones (especially auxin), plant age, sugars, mineral salts and other molecules (Bellini et al, 2014). They may function as signals and induce groups of cells to redefine their fate, resulting in and regulating AR.…”
Section: Endogenous Factors Influencing Ar Formationmentioning
confidence: 99%
See 1 more Smart Citation